Effects of high-protein diet on glycemic control, insulin resistance and blood pressure in type 2 diabetes: A systematic review and meta-analysis of randomized controlled trials. Issue 6 (June 2020) - Yu, Zhangping; Nan, Fengwei; Wang, Leslie Yingzhijie; Jiang, Hua; Chen, Wei; Jiang, Yu
Summary: Background: Obesity is a well-known risk factor of type 2 diabetes mellitus (T2DM), and it is commonly accompanied by T2DM. It is estimated that almost two thirds of the population with T2DM is also affected by hypertension. Elevated arterial blood pressure would increase the risk for diabetes development. Recently some studies indicated that a high-protein diet was effective for weight loss, and therefore we hypothesized that a high-protein diet could help control blood glucose, mitigate insulin resistance (IR) and improve blood pressure by weight management in T2DM patients. Aim: The study aimed to systematically review the effects of a high-protein diet on glycemic control, IR and blood pressure in T2DM patients. Methods: We searched four electronic databases until May 1st 2018 and included all randomized clinical trials comparing a high-protein diet with other diets. Two reviewers independently identified the trials for inclusion and independently extracted data. Either a fixed- or a random-effects model was used to combine the changes in each outcome from baseline to the end of the intervention. The meta-analysis was performed with RevMan 5.3 software. Results: Twelve articles (thirteen studies) including 1138 T2DM patients met our inclusion criteria. Glycemic control was not significantly different between the high-protein diet and control group, with the changes in fasting plasma glucose (FPG) (−0.13 (95% CI (−0.46, 0.19), p  = 0.43) mmol/L) and HbA1c% (−0.05 (95% CI (−0.18, 0.08, p  = 0.92))) from baseline to the end of intervention. However, the difference in IR between the two groups was statistically significant. Most changes in lipids profiles were favorable. The changes in HDL, LDL, TC, and TG were +0.03 (95% CI (−0.04, 0.11), p  = 0.35) mmol/L,  −0.10 (95% CI (−0.18,  −0.02), p  = 0.02) mmol/L,  −0.21 (95% CI (−0.31,  −0.12), p  < 0.01) mmol/L and −0.19 (95% CI (−0.33,  −0.05), p  < 0.01) mmol/L, respectively. The result of HOMA-IR was −0.27 (95% CI (−0.47,  −0.06), p  < 0.01). Additionally, the difference in blood pressure in terms of systolic blood pressure (−0.57 (95% CI (−2.45, 1.32), p  = 0.55)) and diastolic blood pressure (−0.73 (95% CI (−2.48, 1.02), p  = 0.41)) was not significant. Conclusion: This review showed that a high-protein diet does not significantly improve glycemic control and blood pressure, but can lower LDL, TC, TG and HOMA-IR levels in T2DM patients. Further studies are needed to clarify the effects of a high-protein diet on glycemic control, IR and blood pressure control in T2DM patients.